2018
DOI: 10.4136/ambi-agua.2252
|View full text |Cite
|
Sign up to set email alerts
|

Using the pollutant load concept to assess water quality in an urban river: the case of Carahá River (Lages, Brazil)

Abstract: The objective of this study was to evaluate the water quality of Carahá River in Lages (Brazil), using the concept of pollutant load and comparing the results with the water quality index. Thirteen points along the river were selected and eight collections were carried out over a period of 16 months. The parameters analysed were those required for the calculation of the water quality index (WQI). Flow measurements were also carried out, which enabled the calculation of the polluting load. The results showed th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 16 publications
2
3
0
2
Order By: Relevance
“…Anthropogenic environmental impacts also modify the ichthyofauna (Audry et al, 2004;Quinatto et al, 2018), among them the damming of rivers and construction of hydroelectric plants promote changes in lotic to lentic environments and consequent reduction in fish diversity (Agostinho et al, 2008;Agostinho et al, 2016), moreover, occur simultaneously, introduction and establishment of non-native species (Vitule et al, 2009, Garcia et al, 2019. In the upper Paraná River floodplain, 36% of the records on ichthyofauna are with non-native species (Figure 7A) following with similar proportions, 43% of the studies on ichthyoparasitology (Figure 7B).…”
Section: Discussionmentioning
confidence: 88%
“…Anthropogenic environmental impacts also modify the ichthyofauna (Audry et al, 2004;Quinatto et al, 2018), among them the damming of rivers and construction of hydroelectric plants promote changes in lotic to lentic environments and consequent reduction in fish diversity (Agostinho et al, 2008;Agostinho et al, 2016), moreover, occur simultaneously, introduction and establishment of non-native species (Vitule et al, 2009, Garcia et al, 2019. In the upper Paraná River floodplain, 36% of the records on ichthyofauna are with non-native species (Figure 7A) following with similar proportions, 43% of the studies on ichthyoparasitology (Figure 7B).…”
Section: Discussionmentioning
confidence: 88%
“…Um estudo realizado por Souza 20 e analisado por Quinatto et al 21 avaliou a qualidade das águas do Rio do Sal através da análise de diversos parâmetros, criando um modelo empírico para o monitoramento de recursos hídricos. Os parâmetros avaliados foram Turbidez, Oxigênio dissolvido, pH, coliformes fecais, Residual total e Demanda Biológica de Oxigênio.…”
Section: Discussionunclassified
“…Observando os resultados obtidos e relacionando -os com esta pesquisa, observa-se que o Rio do Sal não teve nenhum tratamento eficaz de descontaminação de suas águas desde 2003 até a realização do presente trabalho em 2011, o qual mostra que o mesmo ain-da permanece contaminado. Dessa forma, torna-se necessário um plano de gestão de controle de suas águas no intuito de torná-las viáveis para o consumo humano e abastecimento da população dependente deste recurso 21 .…”
Section: Discussionunclassified
“…Dalma et al (2015) also found low IQA values in the Embu-guaçu River, metropolitan region of São Paulo. The WQI proved to be a good tool for assessing water quality since it was possible to find the interactions between the parameters in a spatial and temporal distribution as Quinatto et al (2019) and Vieira et al (2019) recommend.…”
Section: Water Quality Index (Wqi)mentioning
confidence: 99%